Comparison of male reproductive success in malaria-refractory and susceptible strains of Anopheles gambiae - Voordouw, Maarten; Koella, Jacob; Hurd, Hilary (My University, 2008)
Background
In female mosquitoes that transmit malaria, the benefits of being refractory to the Plasmodium parasite are balanced by the immunity costs in the absence of infection. Male mosquitoes, however, gain no advantage from being refractory to blood-transmitted parasites, so that any costs associated with an enhanced immune system in the males limit the evolution of female refractoriness and has practical implications for the release of transgenic males.
Methods
Aspects of the male cost of carrying Plasmodium-refractory genes were estimated by comparing the males' immune response and reproductive success among strains of Anopheles gambiae that had been selected for refractoriness or extreme susceptibility to the rodent malaria parasite, Plasmodium yoelii nigeriensis. The refractory males had a stronger melanization response than males from the susceptible line. Four traits were used as correlates of a male's reproductive success: the proportion of females that were inseminated by a fixed number of males in a cage within a fixed time frame, the proportion of females with motile sperm in their spermathecae, the proportion of ovipositing females, and the mean number of eggs per batch.
Results
Although there were significant differences among groups of males in sperm motility and oviposition success, these differences in male reproductive success were not associated with the refractory or susceptible male genotypes. Contrary to expectation, females mated to early emerging refractory males laid significantly more eggs per batch than females mated to later emerging susceptible males. Sperm motility and oviposition success were strongly correlated suggesting that variation in sperm motility influences female oviposition and ultimately male reproductive success.
Conclusions
An increased melanization response in male A. gambiae does not diminish male reproductive success under the experimental protocol used in this study. That refractory males induced ovipositing females to lay more eggs than susceptible males is an interesting result for any strategy considering the release of transgenic males. That sperm motility influences female oviposition is also important for the release of transgenic males.